PELATIHAN KOMPETENSI PROFESIONAL CALON GURU BK DALAM PENGGUNAAN SOSIOMETRI - Nurmawati, Nurmawati; Khodijah, Disa Jahrul; Nuraeni, Fhara Anggi; Zindan, Muhammad Naufal; Ariiq, Farhan; Rahmah, Devita Azkiya; Brawijayanti, Gustia (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
A non-test instrument commonly used to find out the social relationships of students is sociometry. Sociometry is a method of collecting data about students' social interactions. This method is done by asking each individual to choose three other friends who are liked to those who are not liked. The position of each individual relationship that occurs in the group can be measured quantitatively and qualitatively. The form of relationships in this sociometry also varies, including triangular social relationships, centralized social relationships, intimate social relationships, mesh-shaped social relationships, and chain-shaped social relationships. The results of this sociometric processing will obtain an overview in the form of the number of scores obtained by each individual, relationship patterns, relationship intensity, and the position of students in their friendships.